1999
DOI: 10.1002/(sici)1096-9861(19990510)407:3<318::aid-cne2>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the vestibular nuclei to the thalamus in the rat: APhaseolus vulgaris leucoagglutinin study

Abstract: Injections of the anterograde axonal tracer Phaseolus vulgaris leucoagglutinin were made into individual nuclei of the vestibular nuclear complex of the rat to identify specific projections to the thalamus. The results showed that the superior vestibular nucleus and the medial vestibular nucleus, especially its rostral‐to‐middle parts, project to the lateral part of the parafascicular thalamic nucleus (corresponding to the centromedian nucleus in primates), the transitional zone between the ventrolateral thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…The following subcortical structures have been found to project to CM: the mesencephalic, pontine, and medullary reticular formation, the serotonergic dorsal raphe, median raphe and raphe magnus, the cholinergic PPT and LDT nuclei, the nucleus prepositus hypoglossi, the spinal trigeminal nucleus, the medial and lateral vestibular nuclei, the parabrachial complex, the LC, nucleus incertus, distinct regions of the PAG, deep layers of the SC, the nucleus of Darkschewitsch, and the pars reticulata and pars compacta of the substantia nigra (Peschanski and Besson, 1984; Jones and Yang, 1985; Vertes et al, 1986, 1999, 2010; Yamasaki et al, 1986; Hallanger et al, 1987; Vertes and Martin, 1988; Vertes, 1991; Villanueva et al, 1998; Bester et al, 1999; Groenewegen et al, 1999; Shiroyama et al, 1999; Goto et al, 2001; Krout and Loewy, 2000a, 2000b; Krout et al, 2001, 2002; Olucha-Bordonau et al, 2003). In addition, CM receives input from deep cerebellar nuclei, the supramammillary nucleus, zona incerta, and the reticular thalamic nucleus (Haroian et al, 1981; Vertes, 1992; Kolmac and Mitrofanis, 1997; Power et al, 1999; Power and Mitrofanis, 2001).…”
Section: The Limbic Thalamusmentioning
confidence: 99%
“…The following subcortical structures have been found to project to CM: the mesencephalic, pontine, and medullary reticular formation, the serotonergic dorsal raphe, median raphe and raphe magnus, the cholinergic PPT and LDT nuclei, the nucleus prepositus hypoglossi, the spinal trigeminal nucleus, the medial and lateral vestibular nuclei, the parabrachial complex, the LC, nucleus incertus, distinct regions of the PAG, deep layers of the SC, the nucleus of Darkschewitsch, and the pars reticulata and pars compacta of the substantia nigra (Peschanski and Besson, 1984; Jones and Yang, 1985; Vertes et al, 1986, 1999, 2010; Yamasaki et al, 1986; Hallanger et al, 1987; Vertes and Martin, 1988; Vertes, 1991; Villanueva et al, 1998; Bester et al, 1999; Groenewegen et al, 1999; Shiroyama et al, 1999; Goto et al, 2001; Krout and Loewy, 2000a, 2000b; Krout et al, 2001, 2002; Olucha-Bordonau et al, 2003). In addition, CM receives input from deep cerebellar nuclei, the supramammillary nucleus, zona incerta, and the reticular thalamic nucleus (Haroian et al, 1981; Vertes, 1992; Kolmac and Mitrofanis, 1997; Power et al, 1999; Power and Mitrofanis, 2001).…”
Section: The Limbic Thalamusmentioning
confidence: 99%
“…Peripheral vestibular stimulation has been shown to cause strong activation within the thalamus (Deecke et al, 1974 ; Buttner and Henn, 1976 ; Blum et al, 1979 ). Tracing studies performed in rat (Shiroyama et al, 1999 ), cat (Kotchabhakdi et al, 1980 ), and monkey (Meng et al, 2007 ), as well as radiological investigations in humans (Kirsch et al, 2015 ) have demonstrated multiple projections from vestibular nuclei to the thalamus. The primary thalamic targets are the ventrobasal, ventrolateral and intralaminar nuclei and the geniculate bodies (for a recent review, see Lopez and Blanke, 2011 ).…”
Section: Vestibulothalamic Projectionsmentioning
confidence: 99%
“…The neural circuits linking inner ear defects to abnormal striatal function are likely transmitted by the normal auditory and vestibular input pathways, primarily via the thalamus and neocortex (30), but this remains to be demonstrated. Our results also suggest that a neurobiological cause, rather than simply socio-environmental factors, contributes to the high incidence of behavioral disorders associated with inner ear dysfunction in children and adolescents.…”
mentioning
confidence: 99%